KONTRIBUSI KEPEMIMPINAN DAN KOMPETENSI PROFESIONAL TERHADAP KINERJA GURU - Diny Kristianty Wardany (Pascasarjana Unviersitas Majalengka, 2020)
The research was motivated by the phenomenon of the low performance of teachers. presumably caused by the lack of leadership role of the principal and weak professional competence of teachers, aims to determine: a) Principal leadership, teacher professional competence, and teacher performance; b) The magnitude of the influence of the principal's leadership on teacher performance; c) The magnitude of the influence of teacher professional competence on teacher performance; and d) The magnitude of the influence of the principal's leadership and professional competence on teacher performance. The research used a quantitative approach with survey methods, data analysis consisted of descriptive analysis and verification. The data collection tool used a questionnaire which was distributed to 81 respondents. Data were analyzed using a parametric statistical approach, with a correlation and regression design. The results showed that descriptively, the principal's leadership of professional competence and teacher performance were in good condition, but there were weaknesses in certain aspects. The results of the verification analysis show that: a) The leadership of the principal has an effect on teacher performance; b) Professional competence affects teacher performance; c) Principal leadership and teacher professional competence together have an effect on teacher performance. Conclusion, both partially and jointly with the principal's leadership and teacher professional competence have an effect on teacher performance